PENYULUHAN PEMBUATAN DAN PEMBAGIAN HAND SANITIZER DI KELURAHAN DERINGO - Mulyaningsih, Asih; Permana, Febri; Rusdiansyah, Firdaus; Nursi, Ikhsanudin; Maryati, Maryati; Kenydeklis, Panji Abetnego; Purwanti, Puji; Fauziyah, Vivi (Jurnal Pengabdian Dinamika, 2021)
The outreach activity for the manufacture and distribution of hand sanitizers is to educatethepublictobeawareofthespreadofCOVID-19while maintainingcleanlinessand regularly washinghandsusingsoapandrunningwater.Theuse ofhandsanitizersisintended whenaroundushavedifficultywashinghandsusingsoapandwater.The developmentofthe situation withthespreadofCOVID-19hascausedunrestinthecommunity.Oneofthe consequencesis panicbuyingorbuyingmassnecessitiesandhygiene,suchashandsanitizer products. Respondingto this, on August15,2021, the120 ThematicKKM group ofSultan Ageng Tirtayasa University took the initiative to produce hand sanitizers to comply with WHO standards.The120ThematicKKMgroupof SultanAgengTirtayasaUniversitysucceededin producing hand sanitizerswhich werethen distributedto thepeople ofDeringo Villageand the AuliaQolbuFoundationEmpowermentHouse.Throughthis activity,theproductsmadeare usefultoovercometheongoing pandemicand help meettheneedforhand sanitizers.